IMF Survey, Volume 35, Issue 18. (IMF Survey; IMF Survey ;, 2006)
Annual Meetings overview; IMFC communique; World Economic Outlook, chapters I, II, IV; Regional Economic Outlooks: Asia, Africa, Latin America; Low-income countries, high oil prices; Annual Meetings seminar program; Per Jacobsson lecture.